Proyecto “imagen del negro en la Venezuela de hoy”: Una reflexión metodológica - Montañez, Ligia; Sánchez, Ligia M.; Salinas, José F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This paper deals with a quantitative study of a subjective research theme, racial prejudice in Venezuela. It was involved various methodological considerations, among which we can mention the development of an adequate measure. An initial analysis of a pilot study motivated the consideration o unusual epistemological problems, such as the subjective and affective stance of the research (observer). The problems caused by this stance are unavoidable and very important in research on human behavior. A process o self-reflection is present in the first part o the paper. In the following section we include descriptive data o a second version of the instrument and partial results of three items.